2016
DOI: 10.1371/journal.pone.0164598
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Lowers Plasma Angiopoietin-Like 2 in Men with Post-Acute Coronary Syndrome

Abstract: Pro-inflammatory angiopoietin-like 2 (angptl2) promotes endothelial dysfunction in mice and circulating angptl2 is higher in patients with cardiovascular diseases. We previously reported that a single bout of physical exercise was able to reduce angptl2 levels in coronary patients. We hypothesized that chronic exercise would reduce angptl2 in patients with post-acute coronary syndrome (ACS) and endothelial dysfunction. Post-ACS patients (n = 40, 10 women) were enrolled in a 3-month exercise-based prevention pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Muramoto A and his colleagues stated that after a change in life style for a period of 3 months which continued for 6 months, a rapid decline was observed in ANGPTL2 levels in obese individuals that showed 2% or more weight loss [ 35 ]. Thorin-Trescases and colleagues reported in patients with acute coronary syndrome after 3 months of physical training, which the plasma levels of ANGPTL2 decreased to 26%, while body mass, lean and fat mass, waist circumference, and BMI were not affected by the exercise training program [ 36 ]. Also, in the study of Piche, M.E and colleagues found that after a bariatric surgery, a relative decrease (0% at 6 months, 18% at 1 year) in ANGPTL2 levels did not reflect a drastic decrease in weight (27% at 6 months, 37% at 1 year) and the two studies suggested that the decrease in ANGPTL2 levels after bariatric surgery or physical training is not a marker of adiposity [ 37 ], and it is stated that this factor also secreted by other cells such as the heart, kidneys, endothelial cells and macrophages [ 13 , 14 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Muramoto A and his colleagues stated that after a change in life style for a period of 3 months which continued for 6 months, a rapid decline was observed in ANGPTL2 levels in obese individuals that showed 2% or more weight loss [ 35 ]. Thorin-Trescases and colleagues reported in patients with acute coronary syndrome after 3 months of physical training, which the plasma levels of ANGPTL2 decreased to 26%, while body mass, lean and fat mass, waist circumference, and BMI were not affected by the exercise training program [ 36 ]. Also, in the study of Piche, M.E and colleagues found that after a bariatric surgery, a relative decrease (0% at 6 months, 18% at 1 year) in ANGPTL2 levels did not reflect a drastic decrease in weight (27% at 6 months, 37% at 1 year) and the two studies suggested that the decrease in ANGPTL2 levels after bariatric surgery or physical training is not a marker of adiposity [ 37 ], and it is stated that this factor also secreted by other cells such as the heart, kidneys, endothelial cells and macrophages [ 13 , 14 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Details on the inclusion and exclusion criteria have been previously described elsewhere. 17,18 Importantly, AMI (ST elevation myocardial infarction or non-ST elevation myocardial infarction) was based on the universal definition. 19 For more detailed information on the exclusion criteria see section S1 of the Supporting Information.…”
Section: Participantsmentioning
confidence: 99%
“…But it is not so clear-cut. We reported that in overweight patients with acute coronary syndrome, 3 months of physical training reduced significantly plasma ANGPTL2 levels independently of a weight loss: while ANGPTL2 levels were reduced by 26% in men with acute coronary syndrome, body mass, lean and fat mass, waist circumference, and BMI were not affected by the exercise training program [ 8 ]. On the other hand, we recently reported that in severely obese patients, the relatively low reduction of ANGPTL2 levels after bariatric surgery (0% at 6 months, 18% at 1 year) does not reflect the drastic weight reduction (27% at 6 months, 37% at 1 year), but rather improvement in diabetes, dyslipidemia, and inflammation [ 60 ].…”
Section: Sources Of Circulating Angptl2mentioning
confidence: 99%
“…In accordance with this hypothesis, we recently reported that in patients with severe chronic kidney disease, high ANGPTL2 circulating levels measured after kidney transplantation were associated with high serum endothelin-1 levels [ 48 ]. In addition, we showed that in patients with acute coronary syndrome, the reduction of ANGPTL2 levels induced by the training program correlated with endothelial function measured at baseline: better initial endothelial function correlated with lower ANGPTL2 levels reached after exercise [ 8 ]. Dysfunctional (mouse, human) and/or senescent (human) endothelial cells could therefore produce ANGPTL2, contributing to the proinflammatory environment.…”
Section: Sources Of Circulating Angptl2mentioning
confidence: 99%
See 1 more Smart Citation